University of Maribor: Half a Century of Scholarship and Research - Meško, Gorazd (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
The University of Maribor celebrates its fiftieth anniversary on September 18, 2025. Since 1975, it has undergone an extraordinary development journey, and the second-largest public university in Slovenia has positioned itself as a globally recognised university with a high ranking in Times Higher Education (THE). The development of education, research, and art indicates great achievements and many challenges for the future. The young and, at the same time, mature universities face the same challenges as all other modern universities – to provide quality educational programmes that reflect employment needs, to conduct research that contributes to global science, and to adapt to the needs of sustainable development. The chapter presents the period of the university's formation and its founding, the development of education, research, and art, ensuring quality and sustainable development, international cooperation and internationalisation, social action, and appearance in public media, as well as the management and administration of the university.